SOCIAL STUDIES TEACHERS’ AND TEACHER CANDIDATES’ PERCEPTIONS ON PROMPT FEEDBACK AND COMMUNICATE HIGH EXPECTATIONS - Simsek, Ufuk; Turan, Ibrahim; Simsek, Umit (PEOPLE: International Journal of Social Sciences, 2017)
This study aims to investigate perception of social studies teachers and teacher candidates on the implication of two of the seven principles of good practice in education developed by Chickering and Gamson (1987) at middle school social studies classrooms. To this extend a survey instrument was used to collect data and address the research questions. The total internal reliability coefficient of the scale was calculated as 0.68. The sample of the study consists of 31 Social Studies teachers, 50 second grade and 49 fourth grade Social Studies teacher candidates. The result of the study shows that for principle 4 (prompt feedback) second and fourth grade teacher candidates have more affirmative statements than the teachers, while for principle 6 (communicate high expectations) social studies teachers have more positive statements than 2nd and 4th grade students.